Mechanism of increased microbial autofluorescence by heat treatment. (1st February 2018) - Tominaga, T.; Fujioka, K.; Hijikuro, M.; Tada, T.; Nishikawa, Y.
Abstract: The total direct count (TDC) microbial enumeration method is rapid and suitable for analysing environmental samples containing numerous un‐culturable micro‐organisms. Conventional TDC methods require the addition of a fluorescent stain and are thus unsuitable for automatic monitoring. We unexpectedly found that heated micro‐organisms emit strong autofluorescence. This study was conducted to determine how heating enhances the autofluorescence of bacteria and fungi and to evaluate whether the phenomenon could be exploited to develop a new TDC method. Bacterial autofluorescence was augmented by heating cells at 200°C. ELISA results indicated that levels of advanced glycation end products (AGEs) increased in heated microbes. Catechin, an inhibitor of the Maillard reaction, disrupted the intensification of autofluorescence. These results suggest that the enhanced autofluorescence is associated with the formation of AGEs and that the reaction could be utilized as alternative probe in TDC methods. Significance and Impact of the Study: Autofluorescence of bacteria and fungi was prominently intensified by heat treatment at 200°C. This phenomenon was associated with advanced glycation end products formed in micro‐organisms via the Maillard reaction. The fluorescence signal was strong enough to be utilized as an alternative probe for fluorescent dye in the total direct count method. This phenomenon could be incorporated in an automatic apparatus for microbial enumeration, as it does not require staining.